COVID-19: impact on the urban food retail system and dietary inequalities in the UK. (21st July 2021) - Cummins, Steven; Berger, Nicolas; Cornelsen, Laura; Eling, Judith; Er, Vanessa; Greener, Robert; Kalbus, Alexandra; Karapici, Amanda; Law, Cherry; Ndlovu, Denise; Yau, Amy
ABSTRACT: COVID-19 has focused minds on the resilience of the urban food retail system in supplying adequate food to the whole population. In this commentary, we discuss the impacts on diet of four plausible changes to food retailing in the UK: relocalisation of the food retail system, accelerated uptake of digital grocery, restructuring of fast-food environment and impacts on food banking and emergency food aid. We finish by outlining the challenge for research, policy and planning.